Selection Of Suitable Microorganism For The Production Of L-Glutamic Acid. - S. GANGULY; A. K. BANIK (International Journal of Pharma and Bio Sciences, 2011)
An experimental study was carried out to select suitable microorganism for l-glutamic acid fermentation for this purpose, different regulatory mutant strains namely Micrococcus glutamicus AB1, Psendomonas replivora AB1, Bacillus Cirenlans AB1, Saccharomyces cerevisae AB1 and Aspergillus niger AB1 were subject to fermentation to examine their potency to accumulate l-glutamic acid in the fermentation broth. Saccharomyces cerevisae did not accumulate l-glutamic acid in the fermentation broth. Among the other microorganism studies, Micrococcus glutamicus AB1 accumulated maximum l-glutamic acid (0.7 mg/ml) in the fermentation broth and thus, selected for the further studies.